THE EFFECT OF PROVISION OF CITRIC ACID (CITRIC ACID) AS FEED ADDITIVE ON FCR (FEED CONVERTION RATIO) AND HDP (HEN DAY PRODUCTION) LAYER CHICKEN IN BADAS SUB-DISTRICT, KEDIRI REGENCY) - Prasetyo Agung Kukuh; Rico Anggriawan; Dian Afikasari (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2022)
This study aims to determine the effect of citric acid on the FCR and HDP of laying hens. This research was conducted at Tandjaja Farm located in Lamong Village, Badas District, Kediri Regency for one month starting from March 30 to April 28, 2022. The research method used was an experimental method with 4 treatments and 5 replications. The four treatments were control treatment without citric acid (P0), treatment with 0.1% citric acid level (P1), treatment with 0.3% citric acid level (P2), and treatment with 0.5% citric acid level (P2). P3). The variables observed were feed consumption, egg weight, FCR (Feed Conversion Ratio), and HDP (Hen Day Production). The material used was 200 laying hens of the ISA Brown strain with each treatment 10 tails. Data analysis was carried out by descriptive analysis and quantitative analysis. The data obtained were processed and analyzed using the Analysis of Variant (Anova), then if there was a significant difference, it was continued with Duncan's multiple distance test with a significance level of 5%. The results showed that the application of citric acid as a feed additive to a level of 0.5% in laying hens had no significant effect (P > 0.05) on feed consumption, egg weight, FCR (Feed Conversion Ratio), and HDP (Hen Day Production). However, giving citric acid to P1 with a level of 0.1% and P2 with a level of 0.3% resulted in the best effect on the production of laying hens.